Teach yourself visually Office 2016 - Marmel, Elaine J. (Teach yourself visually, 2016)
"The Microsoft Office suite can be intimidating to the uninitiated, but it doesn't have to be. Through a series of easy-to-follow, full-color two-page tutorials, you'll quickly get up and running on working in Word, excelling at Excel, powering through PowerPoint, keeping in touch on Outlook, managing data in Access, and propelling your way through Publisher like a pro!, "--Amazon.com